2014
DOI: 10.1111/ejn.12715
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine increases light responsiveness of the mouse circadian pacemaker

Abstract: Caffeine is the most commonly used psychoactive stimulant worldwide. It reduces sleep and sleepiness by blocking access to the adenosine receptor. The level of adenosine increases during sleep deprivation, and is thought to induce sleepiness and initiate sleep. Light-induced phase shifts of the rest-activity circadian rhythms are mediated by light-responsive neurons of the suprachiasmatic nucleus (SCN) of the hypothalamus, where the circadian clock of mammals resides. Previous studies have shown that sleep dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 59 publications
(73 reference statements)
4
74
0
Order By: Relevance
“…For example, under very low levels of basal arousal, light could be ineffective, but this effect can be restored by caffeine administration [19]. In agreement with the latter study, our results revealed a positive relationship between arousal and lighting effects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, under very low levels of basal arousal, light could be ineffective, but this effect can be restored by caffeine administration [19]. In agreement with the latter study, our results revealed a positive relationship between arousal and lighting effects.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the presentation of a novel stimulus presumed to increase arousal in hamsters (a new running wheel), attenuated the synchronizing effect of light on circadian rhythms [18]. Moreover, extremely low basal arousal induced by sleep deprivation can block the alerting effect of light upon the activity of suprachiasmatic nuclei, but this effect can be restored by increasing arousal through administration of caffeine [19,20, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…To address this question directly, we employed an in vitro assay based upon bioluminescent reporters of circadian transcriptional rhythms in the well-characterized human U2OS cell line. Period-lengthening in response to chronic caffeine has been reported both at the behavioral level in rodents and flies (11,18,28 ) , as well as at the cellular level in isolated rodent SCN ex vivo and human U2OS cells in vitro (16,18). Human U2OS cells recapitulate the key observation under investigation (18) and similar to the SCN, primarily express the higher affinity, ubiquitous and abundant A 1 adenosine receptor (A 1 R, encoded by the ADORA1 gene) (29,30) as well as PDEs and ryanodine receptors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, adenosine is reported to influence retinal function and transmission of photic information via the retinohypothalamic tract (RHT). Moreover, adenosine administration has been reported to attenuate phase shifts induced by light exposure (42) and caffeine has been shown to enhance the period lengthening effects of light in mice (28). Furthermore, adenosine receptor mRNA is expressed in retinal ganglion cells (43), however whether these include the melanopsin retinal ganglion cells that project to the SCN is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sleep deprivation is known to reduce light responsiveness of the SCN by lowering circadian phase-shifting capacity 85 and decreasing SCN neuronal activity 86, 87 . Thus, both light history and sleep deprivation may account for the rather limited melatonin suppression by constant light, and for the unchanged circadian markers in the study.…”
Section: Discussionmentioning
confidence: 99%